2018
DOI: 10.1186/s12871-018-0579-4
|View full text |Cite
|
Sign up to set email alerts
|

Pleth variability index or stroke volume optimization during open abdominal surgery: a randomized controlled trial

Abstract: BackgroundThe impact of Goal Directed Fluid Therapy (GDFT) based on the non-invasive Pleth Variability Index (PVI) on clinical outcome after abdominal surgery has only sparingly been explored. The purpose of this study was to compare the effect of intraoperative GDFT guided by PVI to a control group using esophageal Doppler on the incidence of complications and length of hospital stay after major abdominal surgery. We hypothesized that there would be no difference between the groups.MethodsThis was a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…However, when compared to esophageal Doppler GDFT in patients requiring colorectal resection, a population more comparable to ours, fluid administration and outcome was not different [27]. Bahlmann et al also showed that PVI and stroke volume optimization assessed by esophageal Doppler during open abdominal surgery had similar outcome [28]. Our results parallel the latter studies and indicate that in low-to-moderate risk abdominal surgery, PVI seems to be an adequate guide for GDFT.…”
Section: Discussionsupporting
confidence: 80%
“…However, when compared to esophageal Doppler GDFT in patients requiring colorectal resection, a population more comparable to ours, fluid administration and outcome was not different [27]. Bahlmann et al also showed that PVI and stroke volume optimization assessed by esophageal Doppler during open abdominal surgery had similar outcome [28]. Our results parallel the latter studies and indicate that in low-to-moderate risk abdominal surgery, PVI seems to be an adequate guide for GDFT.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, standard fluid management strategy was associated with elevated postoperative BUN, blood creatinine, and lactate levels, while fluid administration based on PVI monitoring did not cause any abnormal blood levels. Similarly, in other studies performed on non-geriatric patients it was demonstrated that fluid management under PVI guidance may reduce postoperative blood lactate levels [11,25,26]. Although they were primarily focused on the effects on the duration of hospitalization, the results of Fischer et al study offered opposite results: lactate levels were similar between PVI-guided and routine fluid management groups.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Bahlmann et al compared PVI-based GDFM with esophageal Doppler-based stroke volume assessment in 146 subjects scheduled for open abdominal surgery. [ 25 ] Their results showed that PVI was non-inferior to the esophageal Doppler in terms of the rate of the post-operative complications, and length of hospital stay when used to direct the GDFM. Similar results were derived from the study of Cesur et al, which compared CFM with PVI-based GDFM in subjects undergoing elective colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%